Tailoring cobalt‐free La0.5Sr0.5FeO3‐δ cathode with a nonmetal cation‐doping strategy for high‐performance proton‐conducting solid oxide fuel cells. Issue 5 (29th October 2022) - Yin, Yanru; Dai, Hailu; Yu, Shoufu; Bi, Lei; Traversa, Enrico
Abstract : A nonmetal doping strategy was exploited for the conventional La0.5 Sr0.5 FeO3‐ δ (LSF) cathode, allowing high performance for proton‐conducting solid oxide fuel cells (H‐SOFCs). Unlike previous studies focusing on the utilization of metal oxides as dopants, phosphorus, which is a nonmetal element, was used as the cation dopant for LSF by partially replacing Fe ions to form the new La0.5 Sr0.5 Fe0.9 P0.1 O3‐ δ (LSFP) compound. The H‐SOFC using the LSFP cathode showed a two‐fold peak power density as compared to that using the LSF cathode.